Mixed coating mortars using tire rubber: performance in the face of water - Sakamoto, C. A. [UNESP]; Pagoto, L. M. [UNESP]; Akasaki, J. L. [UNESP]; Pinheiro Melges, J. L. [UNESP]; Fabiano Fioriti, C. [UNESP] (Pontificia Universidad Catolica de Chile, 2023)
This paper evaluated the behavioural performance to coating mortar water with rubberized tyres. #0.60 mm and #1.19 mm grain sizes have been used with the incorporation of 10 and 20% (in volume), replacing the small units. The methodology has elapsed with capillary and drying tests; humidification and drying procedures with mass control, infrared thermography and measurement of humidity. The results indicated that in capillarity and drying the trace A20F (#0.60 mm particle size and incorporation of 20%) had have a low absorption rate and helped in the process of water disposal. In the humidification and drying process, both active as well as passive, the rubber possibly blocks the pores of mass, for the grain traits size #0.60 mm (A10F and primarily A20F) have proven easy to lose water, suggesting that the majority of water absorbed would be concentrated on the surface part of the composite.
Keywords: dry; infrared thermography; Mortar; permeability; thermal analysis